Sociology in Germany A History - Moebius, Stephan (Sociology Transformed,, 2021)
This open access book traces the development of sociology in Germany from the late 19th century to the present day, providing a concise overview of the main actors, institutional processes, theories, methods, topics and controversies. Throughout the book, the author relates the discipline's history to its historical, economic, political and cultural contexts. The book begins with sociology in the German Reich, the Weimar Republic, National Socialism and exile, before exploring sociology after 1945 as a 'key discipline' of the young Federal Republic of Germany, and reconstructing the periods from 1945 to 1968 and from 1968 to 1990. The final chapters are devoted to sociology in the German Democratic Republic and the period from 1990 to the present day. This work will appeal to students and scholars of sociology, and to a general readership interested in the history of Germany. Stephan Moebius is Professor of SociologicalTheory and Intellectual History at the University of Graz, Austria.